Interface arte-moda: tecendo um olhar crítico-estético do professor de artes visuais - Oliveira, Jociele Lampert de (2005)
This research was developed in Arts and Education Line/PPGE. Its purpose was to investigate aspects concerned to fashion-art interface discussion and its implications to build a nowadays visual arts teacher critical-esthetical view. The research subjects were four teachers to be from Visual Arts UFSM Graduation Course. By working this issue with teachers to be we longed for the possibility of thinking about conceptual changes in the way of boarding the theme. Fashion was considered as possibility generating element; and starting by that dialogue fashionart artistic interface can be considered as a common (or different) elements kit between these two knowledge areas. From that tension point between fashion and art we opted for an education theoretic reflection abroad to an art critical comprehension, based on Franz (2003) and Hernández (2002) conceptions, witch grants fashion as an articulator element to visual culture. The employed methodology was based on a qualitative abroad, assisted by participant observation, field diary and documental analysis. Through the investigation results we could attest how those teachers composed their view from practical experiences and conceptual questions about images witch relate fashion-art as well as the critical comprehension related to their own quotidian perception.